Resource exploration type unmanned aerial vehicle provided with solar panel - ZHOU XIN (2015)
The utility model discloses a resource exploration type unmanned aerial vehicle provided with a solar panel. The resource exploration type unmanned aerial vehicle comprises a frame, wherein the frame comprises a frame upper body and a frame lower plate which are fastened and connected by a bolt and a nut; an empennage is installed at the rear end of the frame upper body; a cavity is formed between the frame upper body and a frame lower body; an induction instrument is installed in a cavity in the front end of the frame upper body, and a reserved hole is formed in the front end of the frame upper body; a power device is installed in a cavity in the rear end of the frame upper body; the solar panel is embedded in the frame upper body; resource exploration equipment is installed in a cavity in the middle of the frame upper body, and the frame lower plate is provided with a reserved opening in a position of the resource exploration equipment; unmanned aerial vehicle wheels are installed on the frame lower plate; both the frame upper body and the frame lower plate are approximately triangular; and the front end of the frame upper body is bullet-shaped. The resource exploration type unmanned aerial vehicle disclosed by the utility model is suitable for providing support for resource exploration.